Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3928/01477447-20150603-53
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Contralateral LISS Plate for Vancouver B1 Periprosthetic Femoral Shaft Fractures

Abstract: The authors reviewed all patients treated for periprosthetic femur fractures between March 1, 2007, and January 31, 2010 at the senior author's institution. Demographic features, mechanism of injury, radiographs, and computed tomography scans were reviewed to determine the type and stability of the femoral implant at the time of injury. All Vancouver B1 fractures were treated with a novel technique that used a contoured distal femoral locking plate intended for the contralateral femur and reversed to accommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Successful clinical use of cable‐plate systems has also been reported in man for the treatment of type B1 PPF, which is a common complication in geriatric populations with poor bone quality . Contraindications to using cable‐plate constructs alone include loose or malaligned prostheses, in which arthroplasty revision is preferred, as well as previous periosteal stripping or devascularization because compression from the cables may theoretically further delay bony union …”
Section: Discussionmentioning
confidence: 99%
“…Successful clinical use of cable‐plate systems has also been reported in man for the treatment of type B1 PPF, which is a common complication in geriatric populations with poor bone quality . Contraindications to using cable‐plate constructs alone include loose or malaligned prostheses, in which arthroplasty revision is preferred, as well as previous periosteal stripping or devascularization because compression from the cables may theoretically further delay bony union …”
Section: Discussionmentioning
confidence: 99%
“…Among 39 studies, 10 articles compared the results of Vancouver B1 PFFs treated with ORIF with that of B2 PFFs, and were included in a pair-wise meta-analysis 4 6 7 8 9 16 17 18 21 22) . Twenty-five single cohort studies 1 2 5 20 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43) reported outcomes after surgery for treatment of Vancouver B1 PFFs, and four single cohort studies with Vancouver B2 44 45 46 47) . The studies identified for the meta-analysis included 1,348 femurs: 917 Vancouver B1 PFFs, and 431 Vancouver B2 PFFs ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach of using a reversed contralateral distal femoral locking plating has been reported for the treatment of Vancouver B1 fractures, with a good fracture union rate. However, there is always a risk of failure due to plate weight-bearing [19][20][21]. Addition of an anterior locked plate to the reversed contralateral locking compression-distal femoral plates (LCP-DF) might be a good choice to improve fixation stability and overcome the weight-bearing restriction when using a single-plate system.…”
Section: Introductionmentioning
confidence: 99%